How are alternative clinical placements performed compared to traditional clinical placements during the COVID-19 pandemic? sought through a systematic review and meta‑analysis - Romli, Muhammad Hibatullah; Wan Yunus, Farahiyah; Adam, Siti Khadijah; Salihan, Safuraa (Springer, 2024)
Clinical placement is the essential method of learning in health professions education, but it has been the most disrupted by the COVID-19 pandemic. Institutions of higher education resorted to alternative learning such as telehealth, simulations, and blended-learning for clinical placement to ensure that educational activities continue without delay. However, this raises questions about student competency and necessitates making up for missed in-person hours. A thorough investigation of the effectiveness of alternative clinical placement learning is required. A systematic searching was conducted on ten electronic databases, and the quality of the included articles was assessed using the Medical Education Research Study Quality Instrument (MERSQI). A meta-analysis was conducted by pooling studies with examination mark outcomes. Twenty-four articles were included in the systematic review and nine were included in the meta-analysis. The average MERSQI score for included studies is 11.15. Outcomes on student performance favor alternative placement, whereas perceived-based outcomes have mixed results and are slightly prone to traditional clinical placement. Meta-analysis indicates that alternative learning is either more effective than traditional clinical placement or at least on par with it. There is a discrepancy between perceived outcome and performance assessment regarding the utility of alternative learning to conventional clinical placement. Nonetheless, objective measurement outcomes and the meta-analysis support alternative learning as a reliable learning strategy for clinical education. Alternative learning for clinical placement experience can be improved further by adding more synchronous sessions, and implementing various learning methods, learning activities based on strong instructional design, and at least a short real-setting attachment.